ANALYSIS OF TEACHER RESULTS ON THE USE OF THE PANCASILA CHARACTER ELECTRONIC MODULE FOR EVEN SEMESTER XI CLASS Civics Education Learning - Ida Putri Rarasati; Afriska Yurniawati (Universitas Islam Balitar, 2022)
In the current pandemic situation, all activities are limited. This limitation occurs in all aspects of life, including in the field of education. Based on the results of observations and interviews with PPKN teachers, there are 20 teachers consisting of 8 schools at the SMA/SMK/MA level. These schools include SMAN 1 Srengat, SMAN 3 Blitar City, Muhammadiyan High School Blitar City, SMAN 1 Sutojayan, SMAN 1 Kademanangan, MAN 2 Blitar, Islamic Vocational School 1 Blitar City and Kanigoro Islamic Vocational School. effectively used in distance learning systems. This is due to several factors such as: (1) the form of textbooks and LKS are still in print, while distance learning requires digital-based teaching materials sources, (2) the discussion of material in textbooks and LKS is not in-depth, (3) in LKS and textbooks there are no structured activities in each meeting. The purpose of this study was to find out the response of PPKN class XI teachers to the use of the Ayo Ber character Pancasila electronic module. The research method used is descriptive qualitative by using teacher response questionnaires and interview instruments to explore more in-depth information on the use of modules during product trials. Based on the teacher response test phase, an average percentage of 95% of the XI grade Civics teachers gave a positive response to the developed product.